Do me a syntax: Doggo memes, language games and the internal structure of English. (2019) - Punske, Jeffrey; Butler, Elizabeth
Abstract: This paper provides a sketch of an analysis of an Internet-based language-game known as Doggo. We show that the properties of the Doggo language game illustrate the underlying syntactic structure of English—where the understood verb is derived from two separate pieces. We also provide suggestions for future research into Internet language games.